Encyclopedia of career development - Greenhaus, Jeffrey H.; Callanan, Gerard A.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2006)
Covering a broad range of themes, the contributions to these two volumes represent original material written by leading researchers, scholars & practitioners in the field of career development.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Career development -- Encyclopedias; Vocational qualifications -- Encyclopedias; Vocational guidance -- Encyclopedias; Electronic books